The urgency of the approval of the people's representative council related to the ratification of international trade agreements (analysis of decision of mk-13-puu-xvi-2018) - Diva Pitaloka (Institute for Advanced Science, Social, and Sustainable Future, 2023)
The community feels they are not included in the determination to express consent (consent to be bound) in international trade agreements. The HOUSE OF REPRESENTATIVES is an extension of the people's hand, so the government should ask for the people's approval when deciding to participate in international agreements, especially related to trade. The people's sovereignty must be upheld in a democratic country so that the government cannot ignore the participation of the people. This problem lies in Article 11 of the 1945 Constitution and Article 10 of Law No. 24 of 2000. This article will examine in more depth whether it needs to be included in the criteria for approval by law related to international trade agreements. And is it true that the articles submitted in the petitum of the NGO to the Constitutional Court contradict the 1945 Constitution? This research is a normative legal research with a statutory and conceptual approach. The technique of gathering legal material is carried out by reviewing related literature and analyzing various legal references relevant to the problem under study for further analysis qualitatively and descriptively. This is done by implementing an in-depth and holistic review of multiple connections and evaluating legal materials related to issues. The study results show that all international agreements that have a broad impact, one of which is international trade agreements, should be approved by the House of Representatives in determining whether to participate in the contract. The articles in the petite submitted by NGOs are partly unconstitutional, and finally, international trade agreements should be ratified through law. Ratification, Approval of the House of Representatives, Decision of the Constitutional Court.